Local scour at a bridge abutment along a curved channel - Korkmaz, Meral; Emin Emiroglu, M. (ICE Publishing, 2022)
Few studies have focused on abutments located on curved channels; previous studies have typically focused on straight channels. The present study experimentally examined the local scour that occurs around abutments of different lengths placed on inner and outer banks along a curved channel under clear-water scour flow conditions. The local scour around an abutment in a curved channel is a function of the upstream Froude number, flow intensity, the angle of the bend curvature and the ratios of abutment length to flow depth, abutment length to abutment width and abutment length to channel width. The maximum scour depth around the abutments placed on the outer bank was 1.45 times the scour depth on the inner bank. An empirical equation was developed containing all the dimensional parameters for equilibrium scour depth. The average percentage error of the proposed equation was 2%. © 2022 ICE Publishing. All rights reserved.
Keywords: bridge abutment; bridges; clear-water scour; curved channel; flow characteristics; flow intensity; scour